1983
DOI: 10.1126/science.6836305
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Species of Hemoglobin: Room Temperature Transients and Cryogenically Trapped Intermediates

Abstract: Resonance Raman spectra of photolyzed carbonmonoxyhemoglobin obtained with 10-nanosecond pulses are compared with the spectra of photolyzed carbonmonoxyhemoglobin stabilized at 80 K. In comparing the deoxy with the photodissociated species, the changes in the Raman spectra are the same for these two experimental regimes. These results show that at ambient and cryogenic temperatures the heme pocket in liganded hemoglobin is significantly different from that of deoxyhemoglobin. It is concluded that measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…By this method changes in the properties of photodissociated heme proteins were detected many years ago with optical absorption techniques (4)(5)(6), and studies of the metastable species have been since extended with many other techniques. The relationship between the structure, as inferred from the resonance Raman spectra, of the lowtemperature photoproduct and the transient photoproduct generated at 300 K was discussed recently, and in carbon monoxide hemoglobin, HbCO, it was observed that the differences in the Raman spectra between the stabilized photoproduct and the deoxy preparation at 80 K were the same as those obtained transiently at room temperature with 10-nsec pulses (7). These findings led us to investigate the low-temperature (1.6-100 K) photodissociation of carbon monoxide myoglobin, MbCO, with resonance Raman scattering to determine the properties of the unrelaxed photoproduct and its relationship to the room-temperature transient photoproduct.…”
mentioning
confidence: 90%
“…By this method changes in the properties of photodissociated heme proteins were detected many years ago with optical absorption techniques (4)(5)(6), and studies of the metastable species have been since extended with many other techniques. The relationship between the structure, as inferred from the resonance Raman spectra, of the lowtemperature photoproduct and the transient photoproduct generated at 300 K was discussed recently, and in carbon monoxide hemoglobin, HbCO, it was observed that the differences in the Raman spectra between the stabilized photoproduct and the deoxy preparation at 80 K were the same as those obtained transiently at room temperature with 10-nsec pulses (7). These findings led us to investigate the low-temperature (1.6-100 K) photodissociation of carbon monoxide myoglobin, MbCO, with resonance Raman scattering to determine the properties of the unrelaxed photoproduct and its relationship to the room-temperature transient photoproduct.…”
mentioning
confidence: 90%
“…[1][2][3]13 This band exhibits timedependent spectral shifts after MbCO photolysis, and this has been taken to be an indicator of protein conformational changes in response to bond breaking and recombination. [4][5][6]13,14 The absorption and Stark spectra of deoxyMb are presented in Figure 1, 15 and the values of parameters extracted from an analysis of the Stark spectra are summarized in Table 1. The Stark spectrum shows clear features for bands I and III, as well as for the Q and B bands; the broad negative base line offset below about 16 000 cm -1 may be associated with the Stark effect on band II.…”
mentioning
confidence: 99%
“…Sci. USA 81 (1984) Friedman, Rousseau, and collaborators (20)(21)(22)(23)(24)(25) (27), it is now feasible to study the magnetic properties of photodissociated heme proteins. Such experiments permit a definite answer to the question of the spin state in Mb*.…”
mentioning
confidence: 99%